Impact Of Narrow Money, Monetary Assets And Broad Money On Economic Growth Of Pakistan: A Time Series Study - Saima Munir; Muhammad Niamat Ullah; Bushra Zaman (Kurdish Studies, 2024)
This research study aimed at investigating the impact of Narrow Money (M1t), Monetary Assets (M2t) and Broad Money (M3t) of Monetary Policy Dynamics on Economic Growth of Pakistan for the sample period 1991-92 to 2021-22. Augmented Dickey Fuller (ADF) Test validated integration sequence of stationary at I(0) level in case of GDPt, M1t and M3t and integration order of stationary at I(1) level in case of M2t. Results of Ordinary Least Square (OLS) Regression followed by Autoregressive Distributed Lags Model (ARDL), Bound Test, Error Correction Mechanism (ECM), Variance Inflation Factor (VIF), Heteroscedasticity Test, Lagrange Multiplier (LM) Test, Normality Test, Granger Causality Test, Impulse Response Function and Wald Test found significant influence of tested variables on economic growth in short run and long run. The study concludes the implications in terms of various forms of money supply, where M1t influenced significantly negative impact on economic growth, while M2t influenced significantly positive impact on economic growth, while M3t influenced insignificantly negative impact on economic growth. It may be recommended to the government to utilize money supply forms of monetary policy as effective instruments for economic stability of Pakistan’s economy in short run and long run. The findings underscored the relevance of monetary policy in shaping macroeconomic performance, financial market development and interest rate liberalization for enhanced effectiveness.